(untitled) (Journal of Dhaka Medical College, 2020)
Lactobacillus is a genus of Gram-positive, facultative anaerobic or microaerophilic, rod-shaped, non-spore-forming bacteria.1 In human, they constitute a significant component of microbial flora at a number of body sites, such as the digestive system, urinary system, and genital system. Lactobacillus species are normally a major part of the vaginal microbial flora.2,3,4 As a normal bacterial flora of the vagina the organisms are typically considered contaminants when cultured from urine specimens of female patients. Here we describe the case of a female patient with chronic pyuria and urinary tract symptoms in which Lactobacillus spp. was determined to be the causative microorganism. After proper treatment the patient gets well soon. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 215-217